2019
DOI: 10.3390/pathogens8020061
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Action of Ursolic Acid as a Potential Anti-Toxoplasmosis Agent, and Its Immunomodulatory Effects

Abstract: This study was performed to investigate the mechanism of action of ursolic acid in terms of anti-Toxoplasma gondii effects, including immunomodulatory effects. We evaluated the anti-T. gondii effects of ursolic acid, and analyzed the production of nitric oxide (NO), reactive oxygen species (ROS), and cytokines through co-cultured immune cells, as well as the expression of intracellular organelles of T. gondii. The subcellular organelles and granules of T. gondii, particularly rhoptry protein 18, microneme prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…In this study, we also detected increases of TNF-α and IL-6 mRNA expression levels following chlortetracycline treatment. In a recent study, UA downregulated the expression of the TNF-α and IL-6 in immune cells co-cultured with Toxoplasma (Choi and Lee, 2019). Most studies have found that UA had a strong antiinflammatory activity (Kashyap et al, 2016;Habtemariam, 2019;Rai et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we also detected increases of TNF-α and IL-6 mRNA expression levels following chlortetracycline treatment. In a recent study, UA downregulated the expression of the TNF-α and IL-6 in immune cells co-cultured with Toxoplasma (Choi and Lee, 2019). Most studies have found that UA had a strong antiinflammatory activity (Kashyap et al, 2016;Habtemariam, 2019;Rai et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…In Mycobacterium tuberculosis, UA has shown the ability to inhibit the expression of certain inflammatory cytokines, such as TNF-α, IL-1β, IL-6, and TGF-β [32,33]. UA also has exhibited activity against other intracellular pathogens, such as Toxoplasma gondii, leading to an increased production of NO, ROS, IL-10, IL-12, granulocyte macrophage colony stimulating factor (GM-CSF) and interferon-β, while reducing the expression of IL-1β, IL-6, TNF-α and TGF-β in infected immune cells [34].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment with UA-NLC also decreased the number of tissue parasites in the spleen and liver of animals, and contrastingly it stimulated the immune response. Although some works showed that an active infection would maintain an active immune response [60,61], it is still important to observe that UA as well as related pentacyclic triterpene are able to modulate innate and acquired immune responses [62], as observed in treated animals.…”
Section: Discussionmentioning
confidence: 99%